Analisis Pengurangan Non-Value Added Activities dengan Metode Lean Six Sigma - Iis Azelya; Gesit Thabrani (Universitas Negeri Padang, 2020)
Purpose - This study was conducted with the intention to find out what is included as non-value added activity that is happened in patient’s flow and how to reduce it using lean six sigma method in outpatient department of regional public hospital of Kerinci M.H A Thalib.Methodology - This research uses lean six sigma method with analysis tools in the form of value stream mapping and fishbone diagrams in order to reduce the activities identified as non value added in the outpatient units of the M. H A Thalib general hospital in Kerinci Regency.Finding - The results of the study showed that the lead time required in the flow of patients in this outpatient unit is 7300.27 seconds with a percentage of Process Cycle Efficiency is only 12.22%, and contributing factors such as databases that are not used effectively, delays in medical personnel, lack of infrastructure, and so on. Keywords: Lean Six Sigma, Value Stream Mapping, Fishbone Diagram, DMAIC, Health Service, Reduce, Non-Value Added Activity